2021
DOI: 10.3389/fonc.2021.627202
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Lower Grade Insular Glioma Molecular Pathology Using Diffusion Tensor Imaging Metric-Based Histogram Parameters

Abstract: ObjectivesTo explore whether a simplified lesion delineation method and a set of diffusion tensor imaging (DTI) metric-based histogram parameters (mean, 25th percentile, 75th percentile, skewness, and kurtosis) are efficient at predicting the molecular pathology status (MGMT methylation, IDH mutation, TERT promoter mutation, and 1p19q codeletion) of lower grade insular gliomas (grades II and III).Methods40 lower grade insular glioma patients in two medical centers underwent preoperative DTI scanning. For each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
(54 reference statements)
1
7
0
Order By: Relevance
“…Among the existing studies, only one has focused on insular glioma. Namely, Huang et al found that FA and MD within the tumor ROI can predict molecular biomarkers 16 ; however, a whole-brain fiber bundle-based assessment has been lacking. Thus, microstructural white matter changes revealed by DTI associated with insular glioma remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Among the existing studies, only one has focused on insular glioma. Namely, Huang et al found that FA and MD within the tumor ROI can predict molecular biomarkers 16 ; however, a whole-brain fiber bundle-based assessment has been lacking. Thus, microstructural white matter changes revealed by DTI associated with insular glioma remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The VOIs of lesions were defined as abnormal hyperintense signals on the b0 image ( Figure 1 ) and cerebrospinal fluid signals were avoided. Since the b0 images were part of the DWI sequence, it was simple to align VOIs with other metric maps ( Huang et al, 2021 ). The mean value of each metric map was calculated by FAE 4 ( Song et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, numerous studies have reported that gliomas have specific molecular parameters, such as IDH-mutation ( Chen et al, 2017 ; Kesler et al, 2019 ) and MGMT promoter methylation ( Chen et al, 2017 ). To date, deep neural networks have been utilized to extract dMRI metrics like ADC and FA value, and to assist IDH, MGMT, and other molecule subtype classification and prognosis prediction of glioma patients ( Aliotta et al, 2019 ; Z. Huang et al, 2021 ; Yan et al, 2021 ).…”
Section: Structural Connectome and The Alternations In Gliomasmentioning
confidence: 99%